Measurement of pregnancy rate and foetal loss, and their associations with management practices on reproductive performance of smallholder beef cattle heifers in South Africa - Marble Nkadimeng; Este van Marle-Köster; Nkhanedzeni B. Nengovhela; Fhulufhelo V. Ramukhithi; Johannes M. Rust; Mahlako L. Makgahlela (Tropical Animal Health and Production, 2026)
Understanding reproductive performance of replacement heifers is pivotal for sustainable and profitable farming in any cattle production system. The study assessed reproductive performance of smallholder beef cattle heifers focusing on pregnancy rate (PR); and fetal and calf loss (FCL). Additionally, it investigated herd management factors that influence these traits. A total of 538 heifer records were collected from 40 herds representing five provinces between 2018 and 2019. A secondary application of established seasonal pregnancy diagnosis methods was used to measure PR and FCL. Management factors including body condition score (BCS), age at first mating and calving, breed type, heifer selection, record-keeping, frame size, breeding and calving season were recorded. The Kaplan-Meier method analysed reproductive outcomes, while the Cox proportional hazards model assessed management factors influencing PR and FCL. Results indicated an average of 47% PR and 11% FCL with achievable levels of 60% PR and 0.9% FCL. Majority of heifers conceived between ages four and five years. At three years, 96.19% of heifers had not experienced loss, however, the calf survival probability decreased to 68.17% by five years. The median age for first calving was four, by age five, 72.96% of heifers had calved. The results showed significant effects ( P < 0.05) for breed type, breeding season, BCS, frame size and heifer selection on PR and FCL. Optimizing PR and FCL in smallholder heifers may depend on improving management practices including selection practices of heifers prior to breeding, maintaining optimum BCS and breeding during favourable environmental conditions.

Toxicological Evaluation of Vanillin Flavor in E-Liquid Aerosols on Endothelial Cell Function: Findings from the Replica Project - R. Emma; A. Sun; K. Partsinevelos; S. Rust; V. Volarevic; R. Lesmana; A. Giordano; H. Goenawan; M. I. Barliana; A. Arsenijevic; N. Kastratovic; V. Markovic; et al. (Cardiovascular Toxicology, 2026)
There are challenges that require collaboration among researchers to ensure that tobacco harm reduction strategies are evidence-based. A key challenge is evaluating the safety of flavors in e-cigarettes. Many flavorings are deemed “generally recognized as safe” (GRAS) for ingestion, but this does not guarantee their safety when inhaled. The Replica international research group is dedicated to the replication of studies on tobacco alternatives. As part of this effort, the group conducted a conceptual replication of the vanillin-specific experiments from the study by Fetterman et al. (2018), with the goal of validating their conclusions regarding this compound. We used Aspire Zelos 3 e-cigarette and prepared e-liquids containing propylene glycol, vegetable glycerin, and vanillin. The e-liquids were vaporized under regular (1 Ohm coil, 14 watts) and sub-Ohm (0.3 Ohm coil, 200 °C) settings using a vaping machine, following ISO20768:2018 puffing regime. The vapor was collected into a trapping solution to prepare aqueous extracts for treating human aortic endothelial cells. We evaluated cytotoxicity, oxidative stress, nitric oxide bioavailability, and inflammation addressing some gaps reported in the original study. We observed some harmful effects mostly attributable to ethanol used to trap vanillin, but no harmful effects from vanillin. Our results confirm the endothelial cell dysfunction observed in the original paper, but clarify that these effects are mainly attributable to ethanol and not to vaporized vanillin, indicating that, under the experimental conditions applied, vanillin does not elicit significant adverse effects on vascular endothelial cells. However, further research is needed to confirm its toxicological profile. Graphical Abstract Created in BioRender. https://BioRender.com/rn8dt1m .

Association between cagemate number and risk of death in mice: a time-varying covariate analysis using Cox frailty models - Thirupathi R. Mokalla; Erik S. Parker; Daniel L. Smith; Luis-Enrique Becerra-Garcia; Olivia C. Robertson; Deependra K. Thapa; Mounika Kandukuri; Bret M. Rust; David B. Allison (GeroScience, 2026)
Social housing is desirable for the health and well-being of laboratory mice, as social interactions with conspecifics influence both behavioral and physiological outcomes. Although group housing benefits social species, it can introduce variability in mortality outcomes, and raise welfare concerns, particularly with the emergence of aggression or fluctuating cage densities. Despite this, few studies have evaluated how changes in the number of living cagemates over time are associated with survival, particularly in a sex-specific manner. We analyzed data from the National Institute on Aging’s Interventions Testing Program (ITP; n = 2635 UM-HET3 mice), across three research sites to assess whether housing density influenced longevity differently in male and female mice. Mice were housed in same-sex cages (median = 3 per cage) without reassignment after cagemate death. We applied Cox frailty models incorporating nested random effects for cage and site, with fixed effects for sex, treatment, and time-varying number of living cagemates to estimate hazard ratios, which allowed us to assess the instantaneous risk of death associated with changes in cagemate number. Results showed a significant main effect of the number of living cagemates on mortality and a significant interaction between sex and cagemate count, indicating sex-specific responses. Female mice exhibited a pronounced increase in mortality rate as cage density declined, suggesting a potential role of social buffering in longevity. These findings emphasize the importance of considering social housing dynamics, particularly for female mice, in both experimental design and animal welfare protocols. Graphical Abstract

P18-17 No Evidence of E-Cigarette Aerosol-Induced Cisplatin Resistance in Head and Neck Cancer Cells: Findings from the Replica International Study Group - G. Carota; R. Emma; K. Partsinevelos; S. Rust; A. Sun; A. Giordano; V. Volarevic; R. Lesmana; H. Goenawan; M.I. Barliana; A. Arsenijevic; N. Kastratovic; et al. (Toxicology Letters, 2025)

Risk factors underlining reproductive performance in smallholder beef cattle herds of South Africa - Marble Nkadimeng; Este Van Marle-Köster; Nkhanedzeni B. Nengovhela; Fhulufhelo V. Ramukhithi; Masindi L. Mphaphathi; Johannes M. Rust; Mahlako L. Makgahlela (Tropical Animal Health and Production, 2024)
Improving the historically low reproductive performance of beef cattle in smallholder systems is essential for its productivity and profitability. Therefore, identifying and addressing risk factors associated with low performance in this system present an opportunity for improvement. The study aimed to evaluate the effect of animal and management risk factors on pregnancy rate (PR), fetal and calf loss (FC), calving interval (CI) and days open (DO) in smallholder beef cattle farms. A multi-stage selection approach was conducted in five provinces of South Africa. Cow records (3694) collected from 40 smallholder herds over two years (2018–2019) were analysed. Data on animal and herd management factors including body condition score (BCS), cow age class, breed type, lactation status, culling old/non-productive cows, record-keeping, and breeding and calving seasons were recorded. The GLIMMIX procedure was computed to determine risk factors associated with performance indicators (PR, FC, CI and DO). Risk factors highly associated with performance were breed type, BCS, cow-age class and breeding/calving season ( P ≤ 0.05). Indicators FC, DO and CI increased with decreased BCS, autumn calving seasons, and in first calvers and aged cows. Whereas, PR increased with increasing odds of BCS and breeding seasons between December-March, November-February and January-March. Optimizing reproductive performance in smallholder beef cattle herds may involve managing cow body condition, breeding with adapted genotypes and synchronizing breeding with favourable seasons. Therefore, record keeping and regular monitoring of herd nutrition, climate and breed performance may be significant in improving reproductive performance in smallholder herds.

Uptake of erythromycin by first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), fed live or freeze‐dried enriched adult Artemia or medicated pellets - M A Cook; M B Rust; K Massee; T Majack; M E Peterson (Journal of Fish Diseases, 2003)
The potential to use adult Artemia to deliver erythromycin to first‐feeding sockeye salmon, Oncorhynchus nerka (Walbaum), was investigated in three trials. In the first trial, first‐feeding sockeye were fed live erythromycin enriched adult Artemia or pellets containing equal amounts of erythromycin for 35 days. At the end of the trial, tissue erythromycin concentration of the fish fed the live Artemia was significantly greater ( P μ g mL −1 ; mean ± SEM), than the tissue concentration of the fish fed the pellets (0.72 ± 0.01 μ g mL −1 ). In the second trial, first‐feeding sockeye were fed either live or freeze‐dried bioencapsulated erythromycin (adult Artemia ) or pellets containing erythromycin daily for 21 days. Mean daily erythromycin concentration in fish fed the freeze‐dried Artemia , live Artemia , or pellets did not differ significantly. In the third trial, apparent erythromycin digestibility was determined. Significantly more ( P Artemia (live or freeze‐dried) appears to be greater than uptake from pellets. Freeze‐dried and live Artemia were equally effective at delivery suggesting enriched freeze‐dried adult Artemia could be produced into a highly palatable, consistent, off‐the‐shelf product.

Bioencapsulation of five forms of erythromycin by adult Artemia salina (L.) - M A Cook; M B Rust (Journal of Fish Diseases, 2002)
Uptake of five chemical forms of erythromycin by adult Artemia salina (L.) (erythromycin phosphate – EP, erythromycin stearate – ES, erythromycin estolate – EE, erythromycin hydrate – EH and crystalline erythromycin – CE) was investigated in two trials. In each trial, final erythromycin concentration in Artemia tissue and survival after a 12‐h bioencapsulation period were determined. In the first trial, Artemia tissue concentration after a 12‐h bioencapsulation period was significantly ( P −1 , mean ± SEM) ≈ EH (61.2 ± 3.4 μg mL −1 ) > CE (37.1 ± 10.7 μg mL −1 ) > EP (16.4 ± 7.7 μg mL −1 ) > control. In trial 2, Artemia tissue concentration was also significantly ( P −1 ) > CE (89.1 ± 1.7 μg mL −1 ) > ES (78.9 ± 1.6 μg mL −1 ) > EP (33.4 ± 5.2 μg mL −1 ) > control. Survival was significantly affected by erythromycin form in trial 1 with EP=control (100 ± 0.0%) > ES (74.4 ± 2.0%) > CE (32.2 ± 0.3%) > EH (8.8 ± 4.4%). In trial 2, survival was also significantly affected by erythromycin form with EP=control (100 ± 0.0%) > ES (67.1 ±3.7%) > CE (52.5 ± 7.7%) > EE (5.0 ± 2.5%). Based on both uptake and survival, EP and ES appear to be appropriate compounds for bioencapsulation of erythromycin using live adult Artemia .

Bioencapsulation of erythromycin using adult brine shrimp, Artemia franciscana (Latreille) - T J. Majack; M B. Rust; K C. Massee; . G. W. Kissil; R W. Hardy; M E. Peterson (Journal of Fish Diseases, 2000)
Live adult brine shrimp, Artemia franciscana (Latreille), were enriched with erythromycin to determine if Artemia could accumulate therapeutic levels for subsequent feeding to young fish. Three trials were conducted to determine the erythromycin incorporation and survival rates of enriched Artemia when fed either liposomes containing erythromycin or various erythromycin suspensions. Erythromycin concentration in Artemia fed a liposome suspension was low (∼ 5 μg mL −1 ) relative to Artemia fed the direct suspension (> 100 μg mL −1 ) over the same time period. When enriched with suspensions up to 1 g erythromycin L −1 sea water for 14 h, Artemia survival was not significantly affected ( P > 0.05) relative to controls. Using a suspension of 1 g L −1 , tissue erythromycin concentrations of 109 ± 16 μg erythromycin mL −1 Artemia homogenate (mean ± SEM) were achieved after 12 h. Concentrations above 170 μg mL −1 were obtained using suspensions of 2–5 g L −1 , but Artemia survival significantly ( P

Caste differences in feeding and trophallaxis in the western drywood termite, Incisitermes minor (Hagen) (Isoptera, Kalotermitidae) - B. J. Cabrera; M. K. Rust (Insectes Sociaux, 1999)